The place of statistics in research and national development (2007)
The place of efficient and accurate application of Statistical methodologies (via development relevant research) in national development cannot be over emphasized. The ability to analyze data either manually or with the use of software is just a peripheral aspect of Statistics in the presence of critical issues such as planning and designing of experiment and research works generally. Consequent on this, collaborating with Statisticians become inevitable if meaningful output that would in turn affect national development is expected from a given research work. In this study, we critically accessed the place of Statistics, Statistical methodologies as well as the relevance of the knowledge of Statistics in national development as it sterns from academic and non academic research work in the field of medicine, Engineering, Agriculture, Arts (Humanities), Sciences and Social Sciences. The result of our study shows that Statistics is actively used in all these fields except in the Humanities where a minute percentage of the researchers make use of Statistical tools. Also, the quest for clearer understanding of Statistical methodologies was evident among the respondents who claimed that this would enhance their contribution to national development through quality research output.